Species of Malassezia associated with psoriatic patients - Al-Ammari, Abbas M. M.; Al-Attraqhchi, Azhar A. F.; Al-Jibouri, Mona (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Malassezia spp. are lipophilic unipolar yeasts recognized as commensals of skin that may be pathogenic under certain conditions. Yeasts of the genus Malassezia are known to be members of the skin micro flora of human and other warm-blooded vertebrates. Psoriasis is a common cutaneous disease of unknown etiology, may be triggered by infections, including those due to fungi.Materials and methods: Twenty three patients with psoriasis were included in this study, who attended Al-Kadhumyia teaching hospital / Dermatology department, from the 30th of October 2010 to the 1st of April 2011. Fifteen (15) were males and eight (8)  were females, with the mean age of 44.61±14.65 years (ranging between 3months to 70 years old). The diagnosis was established by clinical examination done by consultant Dermatologist. The site of scraping were face, lower and upper limbs. Control included 14 apparently healthy individuals were randomly selected from entities,  primary and secondary schools in Al-Aubaidi city (10 males and 4 females) with a mean age of 26.83±15.68 years (ranging between 1-70 years old). Both groups were investigated for Malassezia spp., cultivation and identification of Malassezia spp. included Sabouraudَs dextrose agar with and without olive oil.Objectives: Although the role of Malassezia spp. in the pathogenesis of psoriasis is still not fully understood, it is thought that these lipophilic yeasts might be a trigger factor in the exacerbation of psoriatic lesions. Malassezia is associated with the  development of skin lesions in psoriasis because of the response of the scalp lesions in psoriasis to antifungal agents.Results: Malassezia globosa had a high percentage overall Malassezia spp. with psoriatic patients (17.04%). According to gender, males had higher infection rate than females among psoriatic patients. psoriatic patients with age group of (41-50) years had a high percentage among others (56.60%). Oily skinned patients revealed psoriasis disease. Conclusions: From these findings it was suggested that M. globosa reported a high percentage overall Malassezia spp. with psoriatic patients